Kinerja Dinas Perumahan Kawasan Permukiman dan Pertanahan Provinsi Kalimantan Tengah Dalam Peningkatan Jalan Lingkungan Di Kota Palangka Raya - Laksminarti Laksminarti; Laksmi Handayani (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2020)
The Department of Housing, Settlement and Land Areas of Central Kalimantan Province carries out one of the tasks in improving environmental roads in order to facilitate transportation access. In this case the performance can be categorized as good. The theory used as the basis for this research is the measurement of public bureaucratic performance. In the performance measurement there are five indicators used according to Dwiyanto namely 1) Productivity, 2) Service Quality, 3) Responsibility, 4) Responsibility and 5) Accountability. This study uses qualitative research methods because researchers want to understand sociological factors, situations and symptoms or social phenomena in depth and comprehensively. Data collection techniques through observation, interviews and documentation. The primary data in this study are the Head of the Area of ​​Settlement Areas, the Head of the Department of Housing, Settlement and Land Regions of Central Kalimantan Province, and the people of Palangka Raya City. Secondary data from this study are Data on Program Activities of Housing, Settlement and Land Areas of Central Kalimantan Province from 2017-2019 and Data on Achievements of Program Target Activities of Housing, Settlement and Land Services of Central Kalimantan Province from 2017-2019. Based on the results of research on the Performance of the Department of Housing, Residential Areas, and Land in the Improvement of Environmental Roads in the City of Palangka Raya in this case the performance can be categorized well. The planned and implemented program of activities has reached the expected target in terms of reducing slum areas and increasing decent occupancy, especially problems on environmental roads, although not all proposals that come directly from the community are carried out, but all of them are still accommodated and studied by the Disperkimtan. For this reason, it is recommended that the Department of Housing, Settlement and Land Areas of Central Kalimantan Province must conduct regular socialization to the community in providing education related to understanding residential areas. How to create a decent residential area and environment that is maintained in the midst of infrastructure development that will continue to achieve the expected regional development goals and the addition of human resources.